Autism spectrum disorder in children - case study analysis - Juraszek, Karolina; Kalisz, Zdzisława; Glazik, Rozalia; Kucharczuk, Magda; Kalisz, Justyna (Journal of Education, Health and Sport, 2019)
Autism belongs to the group of global neurological developmental disorders. A disturbance in the emotional and social sphere constitutes its specific symptom, together with lack of understanding of other people’s behavior, as well as communicating with them. Most autistic children isolate themselves from the outside world because of too many stimuli, which cause anxiety, fear or self-aggression. The essence is individual therapy, which generalizes and maintains the acquired knowledge and skills, makes the most of the autistic person’s potential, as well as shapes and stimulates psychomotor functions, which are usually reduced by this disorder.The aim of the work was to present the therapeutic path of a boy at different stages of his physical, motor, emotional, social and intellectual development. The functioning of the child before the therapy and the progress made after 4 years were compared. Thorough analysis shows that early therapy has a positive influence on the emotional and social development of an autistic child.To improve the functioning of an autistic child, it is necessary to introduce individual therapies, use a special organization of learning, adapt educational needs and forms of stimulation through fun. The reactions of autistic children are usually atypical in terms of behavior, however, they should not be negatively perceived from the perspective of their otherness. Everyone deserves respect and understanding, and thus society should be open to promoting knowledge about autism.